A new glass sponge genus (Hexactinellida: Euplectellidae) from abyssal depth of the Yap Trench, northwestern Pacific Ocean - Shen, Chengcheng; Dohrmann, Martin; Zhang, Dongsheng; Lu, Bo; Wang, Chunsheng (Zootaxa, 2019)
In this article we report on a hexactinellid sponge new to science, Rhizophyta yapensis gen. et sp. nov., which was collected from the Yap Trench in the northwestern Pacific Ocean at an abyssal depth of 4159–4779 m. Its fungus-like body form with long peduncle and absence of hypodermalia suggest placement within the euplectellid subfamily Bolosominae Tabachnick, 2002, whereas molecular phylogenetic evidence suggests that it is sister to all remaining Euplectellidae Gray, 1867. Its rhizophytous method of attachment to the substrate, hitherto unknown from bolosomine Euplectellidae, a veil of pentactins covering the peduncle, and the presence of toothed discohexasters as the only type of microscleres, clearly characterize it as a new genus. The intraspecific divergence between holotype and paratypes of the new species is examined with both morphological and molecular approaches. This report represents the first record of a hexactinellid sponge from the Yap Trench.